Marketing Mechanisms for Enhancing the Attractiveness of Greek Tourism in International, European, Black Sea, American, and Chinese Markets - Mammassis, Constantinos (Technium Business and Management, 2025)
This paper explores mechanisms for enhancing the attractiveness of Greek tourism in international, European, Black Sea, American, and Chinese markets. Although Greece possesses an exceptional natural landscape, cultural wealth, and historical significance, competing destinations such as Spain, Italy, and Croatia highlight the need for more strategic positioning. By framing Greece as a premium destination, diversification of tourism offerings, and adoption of sustainability practices, the country can strengthen its appeal across different traveler segments. The study emphasizes storytelling, digital and physical accessibility, and partnerships with international stakeholders as critical tools for differentiation. Furthermore, targeted strategies for European, Black Sea, American, and Chinese markets demonstrate the necessity of tailoring tourism development to regional needs. Ultimately, Greece’s long-term competitiveness relies on balancing global visibility with local authenticity while fostering sustainable practices that protect cultural identity and natural resources.